Tin dioxide nano material and preparation method thereof, gas sensor, secondary battery and electric device
By preparing the hollow nanobox form of tin dioxide nanomaterials, the shortcomings of traditional gas-sensitive materials for electrolyte characteristic gas detection are solved, and high sensitivity detection of electrolyte leakage is achieved, reducing the safety hazards of electric vehicle battery packs.
Patent Information
- Application Number
- CN202310833703.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-07
AI Technical Summary
Traditional gas-sensitive materials are difficult to detect the characteristic gases in the electrolyte with high sensitivity and high selectivity, resulting in the leakage of flammable and explosive electrolytes under extreme conditions that cannot be warned in time, which poses safety hazards.
Using tin dioxide nanomaterials, tin dioxide nanomaterials with high specific surface area and characteristic gas selectivity are prepared by preparing hollow nanobox forms, combining the reaction of copper oxide templates and tin tetrachloride, and used for gas sensitivity. The preparation of sensors enables high sensitivity detection of characteristic gases in the electrolyte.
It realizes high selectivity and high sensitivity response to characteristic gases in the electrolyte, can quickly warn of electrolyte leakage, reduce the probability of accidents, and the long-term stability of the material is excellent and suitable for practical applications.
Smart Images

Figure BDA0004328829470000061 
Figure HDA0004328829490000011 
Figure HDA0004328829490000012
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of gas-sensitive materials, and in particular to a tin dioxide nanomaterial and a preparation method thereof, as well as a gas-sensitive sensor, a secondary battery and an electrical device containing the same. Background Art
[0002] As people's pursuit of green production and lifestyle gradually increases, the new energy vehicle industry has developed rapidly. Among them, electric vehicles, as a typical new energy vehicle, have seen an increasing number of vehicles in use year by year, greatly alleviating the problems of energy shortage and environmental pollution. However, during the use of electric vehicles, with the accumulation of time, changes in ambient temperature, and the increase in charge and discharge cycles, the performance of the battery pack will often deteriorate. Even under certain extreme conditions such as overcharging, over-discharging, overheating, and mechanical impact, the flammable and explosive electrolyte inside will leak. If it is not promptly warned and repaired, it may pose a huge safety hazard to personnel, roads, and society.
[0003] The solvent of the electrolyte is mainly non-aqueous organic solvent, such as ethyl methyl carbonate (EMC). When the organic solvent leaks, it turns into organic gas molecules. A gas sensor is a converter that converts the volume fraction of a certain gas into a corresponding electrical signal with the help of a gas-sensitive sensing material, and can be used to detect gas concentration. However, traditional gas-sensitive materials are difficult to detect the solvent of the electrolyte with high sensitivity and selectivity. Summary of the invention
[0004] The present application provides a tin dioxide nanomaterial, which has a high sensitivity and high selectivity response to a characteristic gas EMC in an electrolyte.
[0005] In a first aspect of the present application, a tin dioxide nanomaterial is provided. The tin dioxide nanomaterial is a hollow nanobox. The nanobox includes N planar polygons, where N≤10.
[0006] In some embodiments, 5≤N≤9; optionally, 5≤N≤7.
[0007] In some embodiments, the side length of any planar polygon of the nanobox is 200 nm to 450 nm.
[0008] In some embodiments, the wall thickness of any planar polygon of the nanobox is 5 nm to 30 nm.
[0009] In some embodiments, the specific surface area of the tin dioxide nanomaterial is 50 to 60 m 2 / g.
[0010] In some embodiments, the grain size of the tin dioxide nanomaterial is 3 nm to 8 nm.
[0011] The second aspect of the present application provides a method for preparing a tin dioxide nanomaterial, comprising the following steps:
[0012] preparing a cuprous oxide template;
[0013] The cuprous oxide template, tin tetrachloride and aqueous solvent are mixed for reaction, the obtained reaction solution is subjected to solid-liquid separation, and the solid is collected for washing and annealing to prepare the tin dioxide nanomaterial.
[0014] In some embodiments, preparing the cuprous oxide template comprises:
[0015] Mixing water, a cupric salt and oleic acid to prepare a phase-separated dispersion, wherein the cupric salt is in the water phase;
[0016] heating the phase-separated dispersion to extract the cupric salt into the oleic acid phase and form a complex of the cupric salt and oleic acid to prepare a first reaction solution;
[0017] Adding a base to the first reaction solution to adjust the pH to 9-11.5, and then adding a reducing agent to perform a reduction reaction to prepare a second reaction solution;
[0018] The second reaction liquid is subjected to solid-liquid separation, and the solid is collected and washed to prepare the cuprous oxide template.
[0019] In some embodiments, when preparing the cuprous oxide template, at least one of the following features (1) to (5) is also satisfied:
[0020] (1) The copper(Ⅱ) salt comprises one or more of copper sulfate, copper chloride and copper nitrate;
[0021] (2) heating the phase-separated dispersion to a temperature of 50° C. to 60° C.;
[0022] (3) The base includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide and strontium hydroxide;
[0023] (4) the reducing agent comprises one or more of sodium ascorbate, formaldehyde, sodium bisulfite and ferrous sulfate;
[0024] (5) The molar ratio of the reducing agent to the cupric salt is (0.8-1.2):1.
[0025] In some embodiments, the molar ratio of the cuprous oxide template to the tin tetrachloride is 1:(0.5-0.9).
[0026] In some embodiments, the aqueous solvent includes a mixture of ethanol and sodium chloride aqueous solution.
[0027] In some embodiments, the annealing conditions include: heating to 450° C. to 500° C. for annealing for more than 3 hours;
[0028] Optionally, annealing is performed in an air environment;
[0029] Optionally, the heating rate to 450° C. to 500° C. is 0.3 to 0.7° C. / min.
[0030] In a third aspect of the present application, a gas sensor is provided, comprising a substrate and a sensing material disposed on a surface of the substrate, wherein the sensing material comprises the tin dioxide nanomaterial described in the first aspect or the tin dioxide nanomaterial prepared by the preparation method described in the second aspect.
[0031] In some of the embodiments, the gas sensor is used for monitoring leakage of electrolyte of a secondary battery; optionally, the solvent of the electrolyte includes ethyl methyl carbonate.
[0032] In some embodiments, the gas sensor further includes a heating device for heating the sensing material.
[0033] In a fourth aspect of the present application, a secondary battery is provided, comprising a battery module and a sensor, wherein the sensor comprises the gas sensor described in the third aspect.
[0034] In some embodiments, the battery module includes an electrolyte; optionally, the solvent of the electrolyte includes ethyl methyl carbonate.
[0035] In a fifth aspect of the present application, there is provided an electrical device comprising the secondary battery described in the fourth aspect.
[0036] Effects of the Invention
[0037] The above-mentioned tin dioxide nanomaterial has a high sensitivity and high selectivity response to the characteristic gas EMC in the electrolyte, can monitor the electrolyte leakage, and has a rapid early warning response. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A schematic diagram of a secondary battery according to an embodiment of the present application;
[0039] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0040] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0041] Figure 4A schematic diagram of a battery pack according to an embodiment of the present application;
[0042] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0043] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;
[0044] Figure 7 This is a schematic diagram of the reaction process for preparing the cuprous oxide template according to one embodiment of the present application;
[0045] Figure 8 The scanning electron microscope images of the Cu2O templates prepared in Examples 1-2 and Comparative Example 1 and the tin dioxide cubic nanobox prepared in Example 1;
[0046] Fig. 9 This is a transmission electron microscopy image of the tin dioxide nanobox prepared in Example 1-2;
[0047] Fig.10 (a) XRD pattern and (b) N2 adsorption / desorption isotherm of the SnO2 cubic nanobox prepared in Example 1;
[0048] Fig.11 Gas sensing tests of the SnO2 cubic nanobox prepared in Example 1, wherein (a) is a response value test to 20ppm EMC; (b) a response value test to 10ppb EMC; (c) a response stability test; (d) a response time test; (e) a characteristic gas selectivity test; and (f) a performance attenuation test.
[0049] Fig.12 The gas-sensing tests of the SnO2 nanoboxes prepared in Example 2 and Comparative Example 1 are shown in FIG. 1 , wherein (a) is the characteristic gas selectivity test of the concave octahedral nanobox of Example 2; and (b) is the characteristic gas selectivity test of the regular dodecahedral nanobox of Comparative Example 1.
[0050] Description of reference numerals:
[0051] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION
[0052] Hereinafter, the embodiments of the tin dioxide nanomaterial and its preparation method, gas sensor, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0053] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0056] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0057] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0058] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0059] Compared with other types of sensors, gas sensors have the advantages of being able to respond to changes in gas concentration, low cost, and small size. However, traditional gas sensors have poor selectivity for gas response, and the battery pack or vehicle environment is complex with many interfering gases. How to achieve a highly selective response to the electrolyte still needs further research.
[0060] Some examples of the present application provide a tin dioxide nanomaterial, characterized in that the tin dioxide nanomaterial is a hollow nanobox, and the nanobox includes N planar polygons, N≤10.
[0061] The above-mentioned specific form of tin dioxide nanomaterial has a highly selective response to characteristic gases in battery electrolytes, such as EMC, and has a high response sensitivity. At the same time, the temperature required for the response is low. In addition, the long-term stability of the tin dioxide nanomaterial is excellent, which can better meet the application and production needs.
[0062] It is understandable that the number N of planar polygons contained in the nanobox is a positive integer, including but not limited to: 4, 5, 6, 7, 8, 9, 10. Further, 5≤N≤9. Further, 5≤N≤7. Reasonable control of the number N of planar polygons can optimize the selectivity and response sensitivity of the material. In addition, it is understandable that the nanobox does not exclude the case of containing curved surfaces, such as irregular planes or curved concave or convex surfaces on the basis of a hexahedron (cube) or an octahedron or a similar polyhedron.
[0063] In some examples, the nanobox is in the shape of a hexahedron. It can be understood that a hexahedron refers to a spatial shape with six faces, which is divided into three categories: a cuboid, a parallelepiped, and an irregular hexahedron. Among them, a cuboid, also known as a rectangular solid, is a right quadrangular prism with a rectangular bottom surface, which is composed of six faces, and the relative areas are equal. A cube, also known as a cube, is a special cuboid, and all six of its faces are squares.
[0064] In some examples, the side length of any planar polygon of the nanobox is 200 nm to 450 nm.
[0065] In some examples, the wall thickness of any planar polygon of the nanobox is 5 nm to 30 nm.
[0066] In some examples, the specific surface area of the tin dioxide nanomaterial is 50 to 60 m 2 / g. Specifically, the specific surface area of the tin dioxide nanomaterial includes but is not limited to: 50m 2 / g, 51m 2 / g, 52m 2 / g, 53m 2 / g, 54m 2 / g, 54.49m 2 / g, 55m 2 / g, 56m 2 / g, 57m 2 / g, 58m 2 / g, 59m 2 / g, 60m 2 / g.
[0067] In some examples, the grain size of the tin dioxide nanomaterial is 3nm to 8nm. Specifically, the grain size of the tin dioxide nanomaterial includes but is not limited to: 3nm, 4nm, 5nm, 5.2nm, 5.5nm, 6nm, 7nm, 8nm.
[0068] Some other examples of the present application provide a method for preparing the tin dioxide nanomaterial as described above, comprising the following steps:
[0069] preparing a cuprous oxide template;
[0070] The cuprous oxide template, tin tetrachloride and aqueous solvent are mixed for reaction, the obtained reaction solution is subjected to solid-liquid separation, and the solid is collected for washing and annealing to prepare the tin dioxide nanomaterial.
[0071] The preparation method uses cuprous oxide as a template to prepare tin dioxide nanomaterials, which is convenient for controlling the morphology of the material, and the preparation process is simple, low-cost, and has low requirements on production conditions, which is convenient for promotion and application.
[0072] In some examples, preparing the cuprous oxide template includes:
[0073] Mixing water, a cupric salt and oleic acid to prepare a phase-separated dispersion, wherein the cupric salt is in the water phase;
[0074] heating the phase-separated dispersion to extract the cupric salt into the oleic acid phase and form a complex of the cupric salt and oleic acid to prepare a first reaction solution;
[0075] Adding a base to the first reaction solution to adjust the pH to 9-11.5, and then adding a reducing agent to perform a reduction reaction to prepare a second reaction solution;
[0076] The second reaction liquid is subjected to solid-liquid separation, and the solid is collected and washed to prepare the cuprous oxide template.
[0077] The method for preparing the cuprous oxide template uses oleic acid as the organic phase and is combined with a suitable pH value, which is beneficial to the morphological structure of the cuprous oxide template. Specifically, the pH value adjusted by adding alkali includes but is not limited to: 9, 9.5, 10, 10.5, 11, 11.3, and 11.5.
[0078] Without limitation, the reaction equation for preparing the cuprous oxide template is as follows:
[0079] Cu 2+ +2C 17 H 33 COOH(oleic acid)=Cu(C 17 H 33 COO)2+2H +
[0080]
[0081] In this process, the pH value of the reaction system is regulated by controlling the amount of alkali. When the pH value is 9 to 11.5, the generated cuprous oxide nanoparticles present the desired polyhedral morphology.
[0082] Understandably, the reaction in the reaction of mixing the cuprous oxide template, tin tetrachloride and aqueous solvent is a coordination dissolution reaction. Tin tetrachloride reacts with the cuprous oxide template and generates cuprous chloride on its surface, and cuprous chloride further reacts with chloride ions in the solution to generate a soluble complex. This reaction enables tin dioxide to better replicate the size of the cuprous oxide template, and completely reacts and dissolves the cuprous oxide to generate a hollow structure of a tin dioxide nano-box. Without limitation, the reaction equation experienced by the reaction is as follows:
[0083] SnCl4+xH2O+2Cu2O=SnO2.xH2O+4CuCl
[0084] CuCl+(x-1)Cl - =[CuCl x ] 1-x .
[0085] In some examples, in the process of preparing the cuprous oxide template, the divalent copper salt includes one or more of copper sulfate, copper chloride and copper nitrate.
[0086] In some of the examples, during the process of preparing the cuprous oxide template, the heating temperature of the phase-separated dispersion is 50° C. to 60° C.
[0087] In some examples, during the preparation of the cuprous oxide template, the base includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide, and strontium hydroxide.
[0088] In some examples, during the preparation of the cuprous oxide template, the reducing agent includes one or more of sodium ascorbate, formaldehyde, sodium bisulfite, and ferrous sulfate.
[0089] In some examples, during the preparation of the cuprous oxide template, the molar ratio of the reducing agent to the cupric salt is (0.8-1.2): 1. Specifically, the molar ratio of the reducing agent to the cupric salt includes but is not limited to: 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1.
[0090] In some examples, the molar ratio of the cuprous oxide template to the tin tetrachloride is 1:(0.5-0.9). Specifically, the molar ratio of the cuprous oxide template to the tin tetrachloride includes but is not limited to: 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9.
[0091] In some examples, the aqueous solvent includes a mixture of ethanol and an aqueous sodium chloride solution.
[0092] In some examples, the annealing conditions include: heating to 450° C. to 500° C. and annealing for more than 3 hours. Without limitation, the annealing time includes, but is not limited to: 3 hours, 5 hours, 10 hours, 15 hours, and 20 hours.
[0093] In some of these examples, annealing is performed in an air environment.
[0094] In some of the examples, the heating rate to 450° C. to 500° C. is 0.3 to 0.7° C. / min.
[0095] Some other examples of the present application provide a gas sensor, including a substrate and a sensing material disposed on a surface of the substrate, wherein the sensing material includes the tin dioxide nanomaterial as described above or the tin dioxide nanomaterial prepared by the preparation method as described above.
[0096] The above-mentioned gas sensor, by using the tin dioxide nanomaterial as the sensing material, can realize the highly selective and highly sensitive detection of the organic gas molecules, especially EMC, which are formed when the organic solvent in the electrolyte leaks, and then realizes the monitoring of the electrolyte leakage, and the early warning response is rapid. In addition, compared with other traditional means of identifying organic gas molecules, such as flame ionization detector (FID), that is, ionizing VOCs gas molecules by hydrogen flame, and then detecting with the help of electrodes, or photoionization detector (PID), that is, ionizing gas molecules by high-energy electrodeless ultraviolet lamp and then detecting. The above-mentioned gas sensor can be assembled with the battery to realize in-situ detection, simplify the detection operation, improve the detection efficiency, and can promptly and quickly warn when the electrolyte leak just occurs, reducing the probability of accidents.
[0097] In some examples, the gas sensor is used for monitoring leakage of electrolyte of a secondary battery. Further, the solvent of the electrolyte includes ethyl methyl carbonate.
[0098] In addition, the sensing material needs to cooperate with a certain temperature to achieve response, so in some examples, the gas sensor also includes a heating device for heating the sensing material. Without limitation, the substrate includes a first surface and a second surface relative to each other, the sensing material is arranged on the first surface, and the heating device is arranged on the second surface. The sensing material has a low response temperature. Without limitation, the response temperature is about 130°C. Among them, the heating device can be exemplified by a ruthenium oxide heating coating, which is an electronic heating material that uses lattice vibrations generated by electron transport to achieve heat. The substrate can be exemplified by an electrode sheet, an alumina ceramic sheet, etc.
[0099] Without limitation, the sensing material can be dispersed into a paste by a solvent, applied to the surface of a substrate, and then aged to improve the bonding performance between the sensing material and the substrate, and then welded and packaged to obtain a gas sensor. The aging temperature can be, for example, 200° C. to 500° C., and the solvent can be, for example, one or both of ethanol and water.
[0100] Yet another example of the present application provides application of the gas sensor as described above in monitoring electrolyte leakage in a secondary battery.
[0101] In one example, the solvent of the electrolyte includes ethyl methyl carbonate.
[0102] Yet another example of the present application provides a secondary battery, including a battery module and a sensor, wherein the sensor includes the gas sensor as described above.
[0103] In one example, the battery module includes an electrolyte. Further, the solvent of the electrolyte includes ethyl methyl carbonate.
[0104] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.
[0105] In one embodiment of the present application, a secondary battery is provided.
[0106] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0107] Positive electrode
[0108] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. Polymer material substrate (such as substrates of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.)
[0111] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100% by weight, based on the total weight of the positive electrode film layer.
[0112] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0113] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0114] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder coating unit surface density is 150-350mg / m 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional: 3.3-3.5g / cm 3 The calculation formula of the compacted density is:
[0115] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0116] Negative electrode
[0117] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0118] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0119] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0120] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100% by weight, based on the total weight of the negative electrode film layer.
[0121] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0-30% by weight, based on the total weight of the negative electrode film layer.
[0122] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20 weight %, based on the total weight of the negative electrode film layer.
[0123] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.
[0124] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing such as rolling, a negative electrode sheet is obtained. The negative electrode powder coating unit area density is 75-220mg / m 2 , the compaction density of negative electrode is 1.2-2.0g / m 3 .
[0125] Electrolytes
[0126] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0127] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0128] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is generally 0.5-5 mol / L.
[0129] In some embodiments, the solvent of the electrolyte includes ethyl methyl carbonate (EMC). Without limitation, the solvent of the electrolyte may also include: fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL) One or more. In addition, the solvent of the electrolyte may also include: sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0130] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0131] Isolation film
[0132] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0133] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0134] In some embodiments, the isolation film has a thickness of 6-40 μm, and optionally 12-20 μm.
[0135] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0136] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0137] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0138] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0139] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0140] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0141] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0142] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0143] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0144] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0145] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0146] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0147] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0148] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0149] Example
[0150] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0151] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0152] Example 1
[0153] This embodiment provides a method for preparing cubic tin dioxide nanomaterials. The reaction process diagram is shown in Figure 7 As shown, the steps are as follows:
[0154] (1) Preparation of Cu2O cubic template:
[0155] A 250 mL round-bottom flask was filled with deionized water (about 70 mL), 0.1 M copper sulfate aqueous solution (10 mL) and 5 mL oleic acid. At this time, it can be clearly observed that the solution is divided into two parts, the oleic acid phase is in the upper layer, and the aqueous phase is in the lower layer; heating and stirring to a temperature of about 50° C. to 60° C., when the aqueous phase is colorless and the oil phase turns blue, 1 M NaOH aqueous solution (18.5 mL) is quickly added to the mixed solution in the flask to make the pH value 11.3. After stirring for 15 minutes, it is observed that the solution turns dark blue and is in the form of an oil-in-water emulsion; 0.1 M sodium ascorbate aqueous solution (10 mL) is added, and it is observed that the solution quickly turns yellow; stirring is continued for 1 hour, then taken out and centrifuged (10000 rpm), and the obtained solid is sequentially washed with deionized water, ethanol, and n-hexane for more than three times to prepare a Cu2O cubic template.
[0156] (2) Preparation of SnO2 cubic nanobox:
[0157] 0.02g (0.14mmol) of Cu2O cubic template was weighed and dispersed in 40mL ethanol and 1.2mL sodium chloride aqueous solution (1g / mL), and 2mM SnCl4 ethanol solution (40mL) was added dropwise to the dispersion. Stirring at room temperature, the suspension was observed to gradually change from orange-red to milky white, centrifuged, and the obtained solid was washed three times with deionized water and ethanol respectively; the obtained powder was slowly heated to 500℃ at a heating rate of 0.5℃ / min, and annealed in air for 3 hours, and finally SnO2 cubic nanobox was obtained.
[0158] The main difference between the tin dioxide nanomaterials of Example 2 and Comparative Example 1 and the tin dioxide cubic nanomaterial of Example 1 is that the nanobox morphology is different. Among them, the preparation process of Example 2 is the same as that of Example 1, only the addition amount of 1M NaOH aqueous solution in step (1) is adjusted to 13mL, so that the pH is 9.0, and the prepared tin dioxide nanobox material is in the shape of a concave octahedron; the preparation process of Comparative Example 1 is the same as that of Example 1, only the addition amount of 1M NaOH aqueous solution in step (1) is adjusted to 10.5mL, so that the pH is 8.2, and the prepared tin dioxide nanomaterial is in the shape of a dodecahedron. The schematic diagram of the reaction process is shown as follows. Figure 7 shown.
[0159] Test example:
[0160] (1) Morphology test of SnO2 nanomaterials
[0161] Figure 8 The scanning electron microscope images of the Cu2O templates prepared in Examples 1-2 and Comparative Example 1 and the SnO2 cubic nanobox prepared in Example 1, wherein (a) is the Cu2O cubic template prepared in Example 1, (b) is the Cu2O concave octahedron template prepared in Example 2, (c) is the Cu2O dodecahedron template prepared in Comparative Example 1, and (d) is the SnO2 cubic nanobox prepared in Example 1. Figure 8 It can be seen that the Cu2O cubic template can be dissolved in the form of a complex through the coordination dissolution reaction, and its morphology is completely retained to generate SnO2 cubic nanoboxes, that is, the SnO2 cubic nanobox prepared in Example 1 is in the shape of a cube, the SnO2 nanobox prepared in Example 2 is in the shape of a concave octahedron, and the SnO2 nanobox prepared in Comparative Example 1 is in the shape of a dodecahedron. At the same time, the side lengths of the SnO2 cubic nanoboxes prepared in Example 1 are concentrated in the range of 200nm to 450nm, and the wall thickness is about 5nm to 30nm.
[0162] Fig. 9 TEM images of the SnO2 nanoboxes prepared in Examples 1-2, wherein (a) is the SnO2 cubic nanobox prepared in Example 1, and (b) is the SnO2 concave octahedral nanobox prepared in Example 2.
[0163] Fig.10 (a) XRD pattern and (b) N2 adsorption / desorption isotherm of the SnO2 cubic nanobox prepared in Example 1. Fig.10 It can be seen that the prepared SnO2 cubic nanobox exists in a polycrystalline form and has a small grain size (approximately The XRD pattern was calculated by Jade software. The nanobox structure gives it a rich specific surface area (about 54.49 m 2 / g), which is beneficial to the adsorption-desorption of gases.
[0164] (2) Gas sensitivity test
[0165] Response value, response recovery speed, selectivity and stability are important parameters for measuring gas sensors.
[0166] The SnO2 cubic nanobox prepared in Example 1 is dispersed in ethanol and evenly coated on one side of the alumina ceramic sheet by multiple drops, and the other side of the alumina ceramic sheet opposite thereto is printed with a ruthenium oxide heating material to obtain a preform. The preform is aged at 300°C to improve the bonding performance between the material and the electrode sheet, and the aged electrode sheet is welded and packaged to obtain a gas sensitive sensor element.
[0167] Test process: First, the packaged device is aged, and the test gas of appropriate concentration and dry air as background gas are purchased and connected to the gas measurement platform (Wuhan Bona Intelligent Sense Technology Co., Ltd., BN2914 high-throughput gas-sensitive performance test platform), and the appropriate voltage is adjusted (the voltage in this experiment is about 150°C at 4V) to obtain the appropriate device operating temperature. Dry air is introduced to control the total gas flow in the test chamber to maintain at 500mL / min. After the material current reaches stability, the flow of the test gas and the background gas is adjusted respectively, thereby changing the test gas concentration in the chamber. After that, the semiconductor analyzer is used to observe the change of the current signal and collect the signal. The test gas is disconnected after a certain period of time, and dry air is continued to be introduced until the device recovers. The exhaust gas in the chamber is post-processed through a special waste treatment pipeline.
[0168] The test results are as follows Fig.11 As shown, the EMC response value of the above gas sensor element to 20ppm is 13.9, and has a good linear correlation in the range of 1-20ppm ( Fig.11 (a)). The EMC response value for concentrations as low as 10 ppb is 0.2946 ( Fig.11 (b)) far exceeds the test requirements for battery pack electrolyte leakage. The high response value proves the sensitivity of the sensor to EMC, that is, it has a lower detection limit. The response recovery speed represents the gas adsorption and desorption capacity of the material surface. The faster the response, the stronger the gas adsorption capacity, and the gas sensor can achieve early warning faster. The above gas sensor element has high stability during the five sets of 10ppm EMC tests ( Fig.11 (c)), and it takes only 180s to complete 90% of the response, providing sufficient time to block further leakage and combustion of the electrolyte ( Fig.11 (d)). Selectivity can represent the sensor's ability to detect the target gas in the presence of interfering gases. At the optimal operating temperature of the tin dioxide nanobox, other typical gases commonly found in battery packs (DMC, ethanol, acetone, methane, carbon monoxide, carbon dioxide, except for carbon dioxide at 20ppm, other gases are 10ppm) were tested and found that its response to other gases was significantly lower than that of the characteristic gas EMC ( Fig.11 (e)) confirms that this gas-sensitive material has good anti-interference ability during leakage detection and can effectively cope with the complex gas environment inside the lithium battery during detection. Stability refers to whether the sensor's response to the target gas can be maintained at a high level over a considerable period of time. Good long-term stability is a key performance indicator of EMC sensors. Under laboratory test conditions, the device had almost no performance degradation within six weeks ( Fig.11 (f)), and the material is tightly bonded to the electrode sheet and is not easy to fall off.
[0169] The material performance tests of Example 2 and Comparative Example 1 were carried out in the same manner as the gas-sensing test steps of Example 1. The selectivity test results of the concave octahedral nanobox of Example 2 and the regular dodecahedral nanobox of Comparative Example 1 were as follows: Fig.12 (a) and (b). According to the test results, the regular dodecahedron nanobox of comparative example 1 is not selective for EMC, and the response value is reduced to 3.12109. Although the selectivity and response value of the concave octahedron nanobox of Example 2 are lower than those of Example 1, it still has a certain selectivity for EMC compared with comparative example 1, and the response value is higher than that of comparative example 1.
[0170] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A tin dioxide nanomaterial, characterized in that: The tin dioxide nanomaterial is a hollow nanobox, and the nanobox includes N planar polygons, where N≤10.
2. The tin dioxide nanomaterial according to claim 1, characterized in that: 5≤N≤9; optionally, 5≤N≤7.
3. The tin dioxide nanomaterial according to claim 1 or 2, characterized in that: The side length of any planar polygon of the nanobox is 200nm-450nm.
4. The tin dioxide nanomaterial according to claim 1 or 2, characterized in that: The wall thickness of any planar polygon of the nanobox is 5nm to 30nm.
5. The tin dioxide nanomaterial according to claim 1 or 2, characterized in that: The specific surface area of the tin dioxide nano-box material is 50 to 60 m 2 / g.
6. The tin dioxide nanomaterial according to claim 1 or 2, characterized in that: The grain size of the tin dioxide nanomaterial is 3nm-8nm.
7. A method for preparing a tin dioxide nanomaterial, characterized in that: The steps include: preparing a cuprous oxide template; The cuprous oxide template, tin tetrachloride and aqueous solvent are mixed for reaction, the obtained reaction solution is subjected to solid-liquid separation, and the solid is collected for washing and annealing to prepare the tin dioxide nanomaterial.
8. The method for preparing the tin dioxide nanomaterial according to claim 7, characterized in that: The preparation of the cuprous oxide template comprises: Mixing water, a cupric salt and oleic acid to prepare a phase-separated dispersion, wherein the cupric salt is in the water phase; Heating the phase-separated dispersion to extract the cupric salt into the oleic acid phase and form a complex of the cupric salt and oleic acid to prepare a first reaction solution; Adding a base to the first reaction solution to adjust the pH to 9-11.5, and then adding a reducing agent to perform a reduction reaction to prepare a second reaction solution; The second reaction liquid is subjected to solid-liquid separation, and the solid is collected and washed to prepare the cuprous oxide template.
9. The method for preparing the tin dioxide nanomaterial according to claim 8, characterized in that: When preparing the cuprous oxide template, at least one of the following characteristics (1) to (5) is also satisfied: (1) The copper(Ⅱ) salt comprises one or more of copper sulfate, copper chloride and copper nitrate; (2) heating the phase-separated dispersion to a temperature of 50° C. to 60° C.; (3) The base includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide and strontium hydroxide; (4) the reducing agent comprises one or more of sodium ascorbate, formaldehyde, sodium bisulfite and ferrous sulfate; (5) The molar ratio of the reducing agent to the cupric salt is (0.8-1.2):
1.
10. The method for preparing the tin dioxide nanomaterial according to claim 8 or 9, characterized in that: The molar ratio of the cuprous oxide template to the tin tetrachloride is 1:(0.5-0.9).
11. The method for preparing the tin dioxide nanomaterial according to claim 8 or 9, characterized in that: The aqueous solvent includes a mixture of ethanol and sodium chloride aqueous solution.
12. The method for preparing the tin dioxide nanomaterial according to claim 8 or 9, characterized in that: The annealing conditions include: heating to 450°C to 500°C for annealing for more than 3 hours; Optionally, annealing is performed in an air environment; Optionally, the heating rate to 450° C. to 500° C. is 0.3 to 0.7° C. / min.
13. A gas sensor, characterized in that: The invention comprises a substrate and a sensing material arranged on the surface of the substrate, wherein the sensing material comprises the tin dioxide nanomaterial according to any one of claims 1 to 6 or the tin dioxide nanomaterial prepared by the preparation method according to any one of claims 7 to 12.
14. The gas sensor according to claim 13, characterized in that: The gas sensor is used for monitoring leakage of electrolyte of a secondary battery; optionally, the solvent of the electrolyte includes ethyl methyl carbonate.
15. The gas sensor according to claim 13 or 14, characterized in that: Also included is a heating device for heating the sensing material.
16. A secondary battery, characterized in that: It comprises a battery module and a sensor, wherein the sensor comprises the gas sensor according to any one of claims 13 to 15.
17. The secondary battery according to claim 16, characterized in that: The battery module includes an electrolyte; optionally, the solvent of the electrolyte includes ethyl methyl carbonate.
18. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 16 or 17.
Citation Information
Patent Citations
Preparation method of hollow cube of tin dioxide
CN101928037A
Preparation method of hollow stannic oxide micro-nano particles
CN103848456A
Polyhedral tin dioxide nanoparticle with core-shell structure and preparation method of polyhedral tin dioxide nanoparticle
CN104891558A
Preparation method for hierarchical hollow cubic stannic oxide nanometer particle
CN106629824A
Preparing method for cerium-doped tin-dioxide sensing material for detecting formaldehyde at low temperature
CN109142465A